Genomic characterization of equine influenza A subtype H3N8 viruses by long read sequencing and functional analyses of the PB1-F2 virulence factor of A/equine/Paris/1/2018 - Lena Kleij; Elise Bruder; Dorothée Raoux-Barbot; Nathalie Lejal; Quentin Nevers; Charlotte Deloizy; Bruno Da Costa; Loïc Legrand; Eric Barrey; Alexandre Chenal; Stéphane Pronost; Bernard Delmas; et al. (Veterinary Research, 2024)
Abstract Equine influenza virus (EIV) remains a threat to horses, despite the availability of vaccines. Strategies to monitor the virus and prevent potential vaccine failure revolve around serological assays, RT-qPCR amplification, and sequencing the viral hemagglutinin (HA) and neuraminidase (NA) genes. These approaches overlook the contribution of other viral proteins in driving virulence. This study assesses the potential of long-read nanopore sequencing for fast and precise sequencing of circulating equine influenza viruses. Therefore, two French Florida Clade 1 strains, including the one circulating in winter 2018–2019 exhibiting more pronounced pathogenicity than usual, as well as the two currently OIE-recommended vaccine strains, were sequenced. Our results demonstrated the reliability of this sequencing method in generating accurate sequences. Sequence analysis of HA revealed a subtle antigenic drift in the French EIV strains, with specific substitutions, such as T163I in A/equine/Paris/1/2018 and the N188T mutation in post-2015 strains; both substitutions were in antigenic site B. Antigenic site E exhibited modifications in post-2018 strains, with the N63D substitution. Segment 2 sequencing also revealed that the A/equine/Paris/1/2018 strain encodes a longer variant of the PB1-F2 protein when compared to other Florida clade 1 strains (90 amino acids long versus 81 amino acids long). Further biological and biochemistry assays demonstrated that this PB1-F2 variant has enhanced abilities to abolish the mitochondrial membrane potential ΔΨm and permeabilize synthetic membranes. Altogether, our results highlight the interest in rapidly characterizing the complete genome of circulating strains with next-generation sequencing technologies to adapt vaccines and identify specific virulence markers of EIV.